Efficacy and safety analysis of chemotherapy for advanced colitis-associated colorectal cancer in Japan. Issue 5 (June 2016) - Nio, Kenta; Higashi, Daijiro; Kumagai, Hozumi; Arita, Shuji; Shirakawa, Tsuyoshi; Nakashima, Koji; Shibata, Yoshihiro; Esaki, Motohiro; Manabe, Tatsuya; Nagai, Shuntaro; Ueki, Takashi; Nakano, Michitaka; et al.
Abstract : Chemotherapy for advanced colitis-associated colorectal cancer (CAC) has been insufficiently evaluated. The goal of this study was to clarify the efficacy and safety of chemotherapy for CAC in Japan. CAC patients who were treated with chemotherapy between 2005 and 2015 were retrospectively examined. Twenty-nine patients (median age, 48 years; 23 men) were assessed. Eighteen patients had ulcerative colitis, and 11 had Crohn's disease. Three ulcerative colitis and four Crohn's disease patients were in the active disease phase. Primary tumors were located in the rectum/anus ( n =16), the left colon ( n =9), or the right colon ( n =4). Palliative or adjuvant chemotherapy was performed in 13 and 16 patients, respectively. First-line palliative chemotherapy regimens were as follows: fluorouracil, leucovorin, and oxaliplatin (FOLFOX; n =6), FOLFOX+bevacizumab ( n =3), and others ( n =4). Adjuvant chemotherapy regimens were S-1 ( n =7), oxaliplatin-based ( n =4) and others ( n =5). In palliative chemotherapy, the objective response rate was 15%, and the median progression-free survival and overall survival were 182 and 315 days, respectively. In adjuvant chemotherapy, the 5-year relapse-free survival rate was 78%. Grade 3/4 adverse events (AEs) were observed in 16 patients (55%). Active and remission inflammatory bowel disease patients suffered grade 3/4 nonhematological AEs at an incidence of 71 and 23%, respectively ( P <0.01). Dose reduction was required in 11 patients (38%), eight of whom required it for hematological AEs. Adjuvant chemotherapy for CAC exhibited sufficient efficacy, whereas modest efficacy was shown for palliative chemotherapy for CAC. AEs, particularly nonhematological AEs, were closely associated with disease activity of colitis.